BENTUK PENYAJIAN TARI INEN MAYAK PUKES PADA MASYARAKAT GAYO ACEH TENGAH - Magfirah Fitri (Universitas Negeri Medan, 2015)
This research is a study on the form of presentation of dance Inen Mayak Puke in the Gayo people of Aceh Tengah. In the study researchers used the theories related to research topics such as definition of dance theory form of presentation, the mithod used to discuss the form of presentation of dance Inen Mayak Pukes in the Gayo people of Aceh Tengah. Is a qualitative descriptive method. The population in this study as well as sample, including traditional leaders, artists and dancers. Data collection techniques include literature studies, interviews, observation and documentation. Based on research carried out can be understood that the inen mayak pukes dance is a dance that describes the journey of the story kekeberen (story hereditary) inen mayak. This dance was created in 1960-an bye Mr. Ibrahim Kadir. In the presentation of this dance has an opening stages, namely motion intro entry, later stage of the contents of the range of motion bergegure, karu, semiang, bersedeh ate, mayo ku gue, mujadi atu, uwes and motion of the over. At any atmosphere in the dance accompanied by music as a conduit akat atmosphere and poetry as a determinant of motion. Thn to analyze the form of dance presentation of dance Inen Mayak Pukes will discuss all of the elements contained therein include, motion, accompaniment, clothing, makeup, properties, patterns and stage floor.